A Vignette Study to Derive Health-Related Quality-of-Life Weights for Individuals with Steroid Refractory Chronic Graft-versus-Host Disease Receiving Third-Line Therapy in the United Kingdom - Emma Williams; Luke Skinner; Richard Hudson; Arunesh Sil; Katharina Ecsy; Elisheva Lew; Abdul Jabbar Omar Alsaleh; Elin Gruffydd; Andrew Lloyd; Daniele Avenoso (Journal of Health Economics and Outcomes Research)
# Background Chronic graft-versus-host disease (cGvHD) – a potentially debilitating complication of allogeneic hematopoietic stem cell transplantation – is a rare condition.